POLA KOMUNIKASI ANTARA ETNIS JAWA DAN BATAK DI LINGKUNGAN VI KELURAHAN PANGKALAN MANSYUR - Qonita Afifa; Junedi Singarimbu; Ridwan Nasution (STKIP PGRI TULUNGAGUNG, 2022)
Medan Johor District which is one of the areas in the city of Medan. whose current population consists of various different backgrounds, both economically, educationally, and socio-culturally. In general, the existence of the community consisting of multi-ethnic groups has fostered a spirit of unity and brotherhood within the framework of diversity.The purpose of this study was to find out how the intercultural communication patterns that exist in the community of Medan Johor sub-district, especially in the VI neighborhood of Pangkalan Mansyur sub-district in different cultural circumstances. And the focus of the research studied is the communication between Javanese and Batak ethnic groups. By using a descriptive method with a qualitative approach. Based on the results of data analysis that has been carried out, it is said that the pattern of intercultural communication that occurs in the VI Pangkalan Mansyur sub-district is very well established and harmonious. because the community prioritizes mutual tolerance between each other. Because they live side by side with each other. So if there is something that is against them, the two ethnic groups take a stand with mutual respect, always guided by the state foundation of Pancasila and the motto Bhinneka Tunggal Ika.